THE EFFECTIVENESS OF PUZZLE MEDIA IN TEACHING CAUSE-AND-EFFECT SENTENCES TO EFL LEARNERS IN INDONESIA - Aryanti Nafasatuz Zukhli; Muhlisin Rasuki; Henri Fatkurochman (Universitas Muhammadiyah Metro, 2025)
Effective writing instruction is crucial for English as a Foreign Language (EFL) learners. Nonetheless, teaching cause-and-effect sentences remains a challenge. The current study aims to examine the effectiveness of puzzle media in addressing this challenge. The study employed a pre-experimental, pre-test/post-test design with one group of participants comprising Indonesian high school students. Specifically, this group underwent a pre-test, instructional treatments using puzzle media, and a post-test, along with a questionnaire. The pre-test and post-test were intended to gauge the effectiveness of puzzle media on cause-and-effect sentences as reflected in the participants’ ability to use these constructions before vs. after receiving the instructional treatments, whereas the questionnaire was intended to explore their views of the given instructional treatment. The data, comprising the participants’ scores on the pre-test and post-test, were analysed using a paired-sample t-test. Results reveal a significant difference between pre-test and post-test scores, indicating that puzzle media is effective in teaching cause-and-effect sentences to EFL learners. Furthermore, the analysis of the participants’ responses on the questionnaire indicates that 62.1% of participants found puzzle media engaging and helpful in writing tasks. This study concludes that incorporating puzzle media into EFL writing instruction can enhance learners’ mastery of cause-and-effect sentences and foster a more engaging learning experience.